Assessment of business intelligent based learning management system readiness and acceptance among IIUM students - Mohammad Nasiruzzaman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
Business Intelligent in the education sector is considered as a new issue. In academia, it is also known as Analytics. All types of organization, from business to higher learning institution have a common reason to adopt business Intelligent, specifically to increase efficiency and increase organizational success. However, many targeted users do not use Business Intelligent based learning management services. Literature review suggests the reasons behind is lacked of awareness and techno-phobia. This research principal objective was tantamount to investigate readiness and acceptance of BI based LMS among IIUM students. The study used quantitative method for data collection and analysis. Findings from the analysis show that all factors are crucial for actual use of the system. The research discussion provides a comprehensive view of the significance of the factors. Finally, future implication is referring to additional need for study and understanding built on actual use of the system.